Residual cardiovascular risk in diabetes and obesity: Targeting lipid abnormalities other than LDL cholesterol - Abdulaziz, Lewai S; Khazaal, Faris AK (AL-Kindy College Medical Journal, 2020)
Background: The majorities of statin-treated patients, in whom low-density lipoprotein cholesterol (LDL-C) targets have been achieved, have had recurrent cardiovascular events (CVE) with an absolute rate remain even higher among patients with disorders of insulin resistance, metabolic syndrome (MetS) and type2 diabetes mellitus (T2DM) as compared to patients devoid of these conditions.Objectives: Provide updated key messages of lipid and lipoprotein abnormalities as indicator for cardiovascular disease (CVD) risk in patients with T2DM and obesity, as well as the current evidence-based treatment targets and interventions to reduce this risk.Key messages: The Residual Risk Reduction Initiative (R3I) emphasized atherogenic dyslipidemia (AD) as the chief modifiable contributor to residual cardiovascular risk, especially in conditions associated with insulin-resistant,and call to improve awareness and clinical management.The probable benefit of residual CVD risk reductionsuggests a role for treatment of persistently high TGconcentration even in statin – treated patients, with TG lowering agents including fibrates, niacin, omega polyunsaturatedfatty acids, and other non statin treatment.Therapeutic lifestyle changes including; medically assistedweight loss, physical activity, and dietary changes, as well as improvement of glycemic control should be an adjunct to lipid-lowering pharmacological therapies. Therapy should be concomitantly assessed for treatment tolerance and adequacy with focused laboratory evaluations and patient follow-up. Therapy should be boosted to attain goals according to risk level, and that even more intensive therapy might be warranted in patients with CVD history.